The Application of Translation in International Sports Event Organization and Athlete Communication: Current Status, Challenges, and Strategies - Dandan Tian, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Translation plays a pivotal role in globalization, particularly in the management of international sports events and facilitates effective communication among athletes from diverse linguistic and cultural backgrounds. This study aims to examine the current state of translation practices and the associated challenges in organizing global sports events and facilitating communication among athletes. This study explores the role of translation in international sports communication, with a focus on event organization, athlete interactions, and media coverage. Through case studies, it highlights the best practices and challenges in current translation practices within the global sports industry. The study also offers recommendations to enhance the quality and efficiency of translation, aiming to strengthen support for the international sports sector. The findings of this study advance theoretical understanding of translation within the context of international sports events and athlete communication. They provide a valuable reference for future research and practical applications in the field.